"Itô's Lemma" and the Bellman equation: An applied view - Ken Sennewald; Klaus Wälde (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2005)
Rare and randomly occurring events are important features of the economic world. In continuous time they can easily be modeled by Poisson processes. Analyzing optimal behavior in such a setup requires the appropriate version of the change of variables formula and the Hamilton-Jacobi-Bellman equation. This paper provides examples for the application of both tools in economic modeling. It accompanies the proofs in Sennewald (2005), who shows, under milder conditions than before, that the Hamilton-Jacobi-Bellman equation is both a necessary and sufficient criterion for optimality. The main example here consists of a consumption-investment problem with labor income. It is shown how the Hamilton-Jacobi-Bellman equation can be used to derive both a Keynes-Ramsey rule and a closed form solution. We also provide a new result.
Keywords: D81; C61; D90; G11; 330; Stochastic differential equation; Poisson process; Bellman equation; Portfolio optimization; Consump; Portfolio-Management; Zeitpräferenz; Analysis; Stochastischer Prozess; Theorie; Stochastische Differentialgleichung